Comprehensive Genomic Landscape in Chinese Clear Cell Renal Cell Carcinoma Patients - Huang, Jiwei; Cai, Wen; Cai, Biao; Kong, Wen; Zhai, Wei; Zhang, Jin; Chen, Yonghui; Chen, Shiqing; Bai, Yuezong; Huang, Yiran; Xue, Wei (Frontiers in Oncology, 2021)
Clear cell renal cell carcinoma (ccRCC) is the most common subtype of renal cell carcinoma (RCC). The genomic landscape in Chinese ccRCC needs to be elucidated. Herein, we investigated the molecular features of Chinese ccRCC patients. Genomic profiling of DNA was performed through next generation sequencing (NGS) from Chinese patients with ccRCC between January, 2017 and March, 2020. Clinical information including age, gender, and tumor histology were collected. IHC staining for PD-L1 expression was performed using PD-L1 IHC 22C3 pharmDx assay or Ventana PD-L1 SP263 assay. Data analyses were performed using R 3.6.1. A total of 880 Chinese ccRCC patients who have undergone NGS were included in this study. The most common somatic alterations were detected in VHL (59.7%), PBRM1 (18.0%), SETD2 (12.2%), BAP1 (10.2%), and TP53 (9.4%). Compared with TCGA database, higher mutation frequency of VHL (59.7% vs 50.0%, p <0.001) and TP53 (9.4% vs 3.5%, p <0.001), and lower mutation frequency of PBRM1 (18.0% vs 31.0%, p <0.001) were found in Chinese cohort. Of the 460 patients who were evaluated for PD-L1 expression, 139 (30.2%) had positive PD-L1 expression. The median TMB value was 4.5 muts/Mb (range: 0-46.0). Five (0.7%) patients were identified as MSI-H. Furthermore, 52 (5.9%) patients were identified to carry pathogenic or likely pathogenic germline mutations in 22 cancer predisposition genes. This is the first large-scale comprehensive genomic analysis for Chinese ccRCC patients, and these results might provide a better understanding of molecular features in Chinese ccRCC patients which lead to an improvement in the personalized treatment for these patients.